2017
DOI: 10.1515/jomb-2016-0029
|View full text |Cite
|
Sign up to set email alerts
|

Current Biochemical Monitoring and Risk Management of Immunosuppressive Therapy after Transplantation

Abstract: SummaryImmunosuppressive drugs play a crucial role in the inhibition of immune reaction and prevention of graft rejection aswell as in the pharmacotherapy of autoimmune disorders. Effective immunosuppression should provide an adequate safety profile and improve treatment outcomes and the patients' quality of life. High-risk transplant recipients may be identified, but a definitive prediction model has still not been recognized. Therapeutic drug monitoring (TDM) for immunosuppressive drugs is an essential, but … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(10 citation statements)
references
References 39 publications
0
8
0
2
Order By: Relevance
“…In our another study 12 we also found that MIOX is a significant parameter in the diagnosis of AKI. Similarly, in the present study, we measured the MIOX enzyme to evaluate the effect of RIRS on the kidneys.…”
Section: Discussionmentioning
confidence: 56%
“…In our another study 12 we also found that MIOX is a significant parameter in the diagnosis of AKI. Similarly, in the present study, we measured the MIOX enzyme to evaluate the effect of RIRS on the kidneys.…”
Section: Discussionmentioning
confidence: 56%
“…Possible explanations for the discrepancies in the findings are the use of retrospective study design, the use of different protocols of controlled ovarian stimulation, and different cutoff levels for P4at the time of data analysis. Some studies imprecisely define references for elevated serum P4 levels, and there is variation in the statistical methods used to estimate specific circulating P4 limit values and in the precision of P4measurements that use different immunoassays 12 , 13 . The cutoff of P4 absolute concentrations on the day of hCG administration generally ranges from 0.8 to 2 ng/ml 14 16 .…”
Section: Discussionmentioning
confidence: 99%
“…Numerous sources of pharmacokinetic variability have been recognized in the conventional pharmacokinetic studies of sirolimus (8, 9, 10, 11, 12, 13, 14, 15). Results of these studies suggest the influence of age, food, hepatic impairment and race on sirolimus pharmacokinetic parameters (4, 8, 12, 13, 14, 15). In contrast, only a few population studies have been conducted to assess the pharmacokinetics of sirolimus in kidney transplant patients (16, 17, 18, 19).…”
Section: Introductionmentioning
confidence: 99%
“…Effective immunosuppression plays a crucial role in the successful post-transplantation period. Sirolimus, immunosuppressive which inhibits the cellular response to IL-2 and T-cell proliferation, is approved for the prevention of organ rejection in kidney transplant patients (1, 2, 3, 4). Sirolimus is characterized by highly variable absorption and elimination which result in substantial blood concentrations differences among patients receiving the same doses (5).…”
Section: Introductionmentioning
confidence: 99%